Market Structure and Competition During Economic Transformation - David Benček; Hannah Rosenbaum; John P. Weche (Wirtschaftsdienst)
Abstract The German economy is facing major challenges. In addition to digitization and climate change, a possible deglobalization is also being discussed in the wake of the COVID 19 pandemic and Russia’s attack on Ukraine. In particular, the disruptions and uncertainties recently observed in international value chains provide an incentive for companies to rethink and restructure supply chains. The re-nationalization of production processes contributes to greater security of supply, but sometimes at the price of higher production costs. Ultimately, these developments can affect existing market structures and competition. A decrease in the intensity of competition in the economy as a whole could have far-reaching macroeconomic consequences. Among those are, for example, declining private investment, a declining wage share, increasing income inequality, declining productivity growth and effects on inflation.